A two-period carbon tax regulation for manufacturing and remanufacturing production planning. (February 2019) - Dou, Guowei; Guo, Hainan; Zhang, Qingyu; Li, Xiaodong
Highlights: Remanufacturing improves both economic and environmental benefits under a two-period carbon tax regulation. Improving the first (second) period tax price always decreases (may enlarge) the overall emission. The overall emission can be effectively controlled by raising one carbon tax price. The overall emission could either increase or decrease in the emission saving parameter. Green technology benefits the environment with a low remanufacturing emission intensity. Abstract: The tax price in a carbon tax regulation may vary from time to time. In this paper, we model a manufacturer who produces new products in the first period and makes new and remanufactured products in the second period under carbon tax regulation where the tax price differs over the two periods. It is shown that improving the first period tax price always decreases the total emission, while improving the second period tax price may enlarge the overall emission. With the decrease of the remanufacturing emission intensity, the overall emission could either increase or decrease. To effectively control the total emission, the tax price could be raised selectively by the regulator according to the manufacturer's production decision and the characteristic of remanufacturing. In addition, subsidizing strategy for employing green technology during remanufacturing pays off in obtaining environmental benefit only when the original remanufacturing emission intensity is low enough. With this two-period tax regulation, regulators are enabled to improve both the economic and environmental benefits.